감성어휘을 통한 디지털이미지 크리에이팅에 관한 연구 - 서미라(Mi-Ra Seo); 박상진(Sang-Jin Park); 곽훈성(Hoon-Sung Kwak) (한국콘텐츠학회 논문지, 6(4), 2006)
Such changes that the digital paradigm brought propels a change of the value system itself in the existing society so that a way of thinking that differentiates oneself from others is getting much stronger. As public interests are higher in the image production on the internet, such authoring environments as development of related technologies, expansibility of information, and systematization of available information continue to change. Therefore, a variety of unique image presentations that fit to the changed environments are necessary and an expression method is indispensable for such image production. This study focuses on digital image creating in which a synectics method is applied. It suggests digital image application methods and examples that contain not just simple image distortion or variation but intrinsic significance. It is believed that it will be of good use to produce a variety of unique and innate digital images in the end. 디지털 방식이 가져온 변화는 기존사회 가치체계 자체의 변화를 추구하며 남과는 다르게 차별화 시키고자하는 사고방식이 그전보다 훨씬 강해지고 있다. 따라서 변화된 환경에 맞는 다양하고 독창적인 이미지 연출이 필요하며, 이미지 제작을 위한 표현 방법이 필요하다. 본 논고는 디지털 이미지 크리에이팅에 관한 것으로 먼저 개발 대상을 선정하고, 감성차원을 통해 개발 대상에서 연상되는 감성어휘를 추출한다. 이후 대상간의 연계성을 시네틱스의 상징적 유추를 통해 시각화시키는 프로세스로 진행된다. 본 논고에서 활용된 시네틱스 기법은 그 특성상 대상의 본질적인 의미를 파악하는 기회를 제공하여 그 해결책의 본질에 대한 새로운 통찰력과 접근방법을 찾을 수 있기에 문제 정의와 문제 해결에서 창조성을 자극시키는 도구로써 사용되었다 궁극적인 연구 목적은 단순한 이미지의 왜곡이나 변형이 아니라 본질적인 의미가 담긴 디지털 이미지 제작의 방법 모색과 프로세스 접근에 대한 태도의 전환을 통해 독창적이고 다양한 디지털 이미지 연출에 도움이 되고자 함이다.